Physical Integrity - Riess, Christian (Springer Science and Business Media Deutschland GmbH, 2022)
Physics-based methods anchor the forensic analysis in physical laws of image and video formation. The analysis is typically based on simplifying assumptions to make the forensic analysis tractable. In scenes that satisfy such assumptions, different types of forensic analysis can be performed. The two most widely used applications are the detection of content repurposing and content splicing. Physics-based methods expose such cases with assumptions about the interaction of light and objects, and about the geometric mapping of light and objects onto the image sensor.
CRIS-Team Scopus Importer:2022-04-22